2021
DOI: 10.7903/cmr.20349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Workplace Spirituality on Perceived Organizational Support and Job Performance among University Administrative Employees

Abstract: The need to fully exploit human resources for competitive advantage has brought spirituality into the work setting. The study set to examine the predictive relationship workplace spirituality has with perceived organizational support and job performance. The assessment is premised on Rego and Cunha's five-workplace spirituality dimension model. This study adopted a correlational design with a self-administered questionnaire of 118 university administrative employees at a university. The research hypotheses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
4
9
0
2
Order By: Relevance
“…Likewise, lower organizational support will decline the employee-organization relationship, decreasing the temporary staff performance in the organization. This hypothesis is supported by researchers (Shih et al, 2011;Bal & Tan, 2014;Li et al, 2020;Nwanzu & Babalola, 2021;Astuty & Udin, 2020). 1 shows that all composite reliability and Cronbach's alpha figures were within the acceptable range.…”
Section: Perceived Organizational Support and Temporary Staff Perform...supporting
confidence: 56%
See 1 more Smart Citation
“…Likewise, lower organizational support will decline the employee-organization relationship, decreasing the temporary staff performance in the organization. This hypothesis is supported by researchers (Shih et al, 2011;Bal & Tan, 2014;Li et al, 2020;Nwanzu & Babalola, 2021;Astuty & Udin, 2020). 1 shows that all composite reliability and Cronbach's alpha figures were within the acceptable range.…”
Section: Perceived Organizational Support and Temporary Staff Perform...supporting
confidence: 56%
“…Furthermore, research was conducted in Nigeria on university administration; the result showed a positive and significant effect of P.O.S. on employee performance (Nwanzu and Babalola, 2021). Another research in India confirmed this hypothesis on the impact of P.O.S.…”
Section: Perceived Organizational Support and Temporary Staff Perform...mentioning
confidence: 86%
“…Also, to prevent and reduce the level of socially desirable responses, the cover letter made the participants understand that giving their honest responses would reflect the true purpose of the research (Rodriguez-Ardura & Maseguer-Artola, 2020). The response scaling adopted (5-point Likert scale) was easy for the participants to understand and helped prevent potential response bias from the participants (Nwanzu & Babalola, 2021). Statistically, the correlation matrix technique was utilized to assess the impact of common method variance in the study.…”
Section: Common Methods Variancementioning
confidence: 99%
“…The need for organizations to utilize human resources to provide competitive advantages for organizations has given rise to the concept of workplace spirituality (Nwanzu and Babalola, 2021). Employees are expected to bring their intellect and their complete selves into the organizational fold, creating an environment conducive to spirituality (Nwanzu and Babalola, 2021). Ashmos and Duchon (2000) described workplace spirituality as an individual recognising their spiritual nature, where their inner values must be nurtured in the work environment.…”
Section: Introductionmentioning
confidence: 99%
“…Spirituality and positive mood of employees positively influence employee work attitudes so that they can increase productivity and impact the organisation's long-term effectiveness (Milliman et al, 2003). Previous research found that workplace spirituality has a positive relationship with job performance (Jena, 2022;Nwanzu and Babalola, 2021;Do, 2018).…”
Section: Introductionmentioning
confidence: 99%